2014
DOI: 10.4184/asj.2014.8.4.400
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Paracetamol on Postoperative Pain after Lumbar Discectomy

Abstract: Study DesignA randomized, double-blinded controlled trial.PurposePostoperative pain relief especially using analgesic drugs with minimal side effects has considerable clinical importance. This study aimed to examine the effect of intravenous paracetamol on pain relief after lumbar discectomy as a major surgery.Overview of LiteraturePatients undergoing lumbar discectomy experience a high degree of lumbar pain. Some authors emphasize the use of intravenous paracetamol to improve postoperative pain and increase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…The 2 RCTs that tested tramadol found that it did not reduce pain scores but it was more effective than placebo and less effective than fentanyl in reducing opioid consumption . The 2 RCTs that tested paracetamol found that it was more effective than placebo and less effective than dexketoprofen in reducing pain scores . The RCTs that tested systemic lidocaine, ketorolac, and NSAIDs (tenoxicam) led to controversial results .…”
Section: Resultsmentioning
confidence: 99%
“…The 2 RCTs that tested tramadol found that it did not reduce pain scores but it was more effective than placebo and less effective than fentanyl in reducing opioid consumption . The 2 RCTs that tested paracetamol found that it was more effective than placebo and less effective than dexketoprofen in reducing pain scores . The RCTs that tested systemic lidocaine, ketorolac, and NSAIDs (tenoxicam) led to controversial results .…”
Section: Resultsmentioning
confidence: 99%
“…In patients undergoing lumbar discectomy post-operative pain was adequately controlled by starting intravenous acetaminophen 20 minutes before start of surgery. 4 In patients undergoing total abdominal hysterectomy it was concluded that a pre-emptive intravenous dose of 1 gm provides good quality of postoperative analgesia and results in a decreased consumption of morphine. 5 In This study also we found that intravenous formulation was better overall in post-operative pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…Here in this study we wish to compare the efficacy in between the two in controlling post-operative pain after general anaesthesia for short duration surgeries. [1][2][3][4][5] Study aimed to compare the efficacy of 1 gram acetaminophen oral dose with 1 gram acetaminophen intravenous dose, to estimate whether oral route acetaminophen is effective in controlling post operative pain and to compare the pain scores for oral and intravenous acetaminophen at each time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Acetaminophen (Paracetamol) has been successfully used for management of postoperative pain in different types of operations. 7,8 Studies conducted in the past to assess the efficacy of acetaminophen in attenuating the DOI: 10.29309/TPMJ/2020.27. 2.3921 hemodynamic presser response 9,10 found it to be efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…Acetaminophen, a non-opioid analgesic, does not cause adverse effects associated with opioids such as respiratory depression, nausea and vomiting. 7,8 Also, it has few contraindications and no significant drug interactions. 12 Keeping in view a better profile of acetaminophen in regard to adverse effects, contraindications, and interactions with other drugs, we wanted to find out if it could be used instead of nalbuphine in attenuating the presser response during orotracheal intubation while administering general anaesthesia.…”
Section: Introductionmentioning
confidence: 99%